Pengembangan E-LKPD Matematika Berbasis Liveworksheets Menggunakan Konteks Masjid Suro Palembang - Fitri, Diana; Syutaridho, Syutaridho; Nizar, Harisman (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2024)
This research aims to produce e-worksheets on the volume of cuboid and cylinder that are valid, practical, and have a potential effect on the mathematical problem solving ability of seventh grade students. This research is based on the Indonesian Realistic Mathematics Education (I-RME) approach using the context of the Palembang Suro Mosque with a development research method through the Tessmer research model which consists of 2 stages. The first stage is the preliminary stage (preparation and design stage) and the second stage is the formative evaluation stage (self evaluation, expert review, one-to-one, small group, and field test). The data collection techniques used were validation sheets, questionnaires, interviews, and tests. The results of this research indicate that (1) the e-worksheets developed is